Carbon fiber, method for surface modification thereof, and carbon fiber reinforced composite
Patent Information
- Application Number
- CN202610836612.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-08-28
AI Technical Summary
然而,碳纤维表面惰性高、光滑且化学活性低,导致其与树脂基体的界面粘结强度不足,成为制约复合材料整体力学性能(尤其是层间剪切强度和抗冲击性能)的关键瓶颈
本发明提供了一种工艺简单、可控性强、效果显著的碳纤维表面改性方法。该方法通过等离子体预活化和化学气相沉积技术相结合,在碳纤维表面原位生长均匀的纳米级二氧化硅颗粒,从而协同提升其表面粗糙度与化学活性,最终实现碳纤维复合材料界面性能的提升。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon fiber composite materials technology, and more specifically, to carbon fibers, methods for surface modification of carbon fibers, and carbon fiber reinforced composite materials. Background Technology
[0002] Carbon fiber is widely used in aerospace, wind power generation, sporting goods, and the automotive industry due to its excellent properties such as high specific strength, high specific modulus, and corrosion resistance. However, the high inertness, smoothness, and low chemical reactivity of carbon fiber surfaces result in insufficient interfacial bonding strength between it and the resin matrix, which has become a key bottleneck restricting the overall mechanical properties of composite materials (especially interlaminar shear strength and impact resistance).
[0003] In view of this, the present invention is proposed. Summary of the Invention
[0004] The purpose of this invention is to provide carbon fibers and methods for surface modification thereof, as well as carbon fiber reinforced composite materials, in order to improve at least one of the problems mentioned in the background art.
[0005] This invention is implemented as follows: In a first aspect, the present invention provides a method for surface modification of carbon fibers, comprising: Carbon fibers are subjected to plasma treatment in a mixed atmosphere at a power of 50-500W for 1-30 minutes to obtain pretreated products. The mixed atmosphere contains oxygen at a volume ratio of 1-18%. The pretreated sample was placed in a vapor deposition chamber, a silicon source was introduced, and nano-silica particles were deposited on the surface of the pretreated sample by vapor deposition. The deposition temperature was 200~600℃, the deposition pressure was 100~5000 Pa, and the deposition time was 5~120 min. After deposition, the carbon fibers were cooled to room temperature under an inert atmosphere to obtain surface-modified carbon fibers.
[0006] In an optional embodiment, the mixed atmosphere is a mixture of an active gas and an inert gas, wherein the active gas is at least one of air and oxygen. The volume ratio of active gas to inert gas is 1:5~20.
[0007] In an optional embodiment, the silicon source is selected from at least one of tetraethyl orthosilicate, silicon tetrachloride, and methyltriethoxysilane.
[0008] In an optional implementation, the silicon source is carried into the vapor deposition chamber by a carrier gas; Alternatively, the silicon source is carried into the vapor deposition chamber by a carrier gas bubble.
[0009] In an optional embodiment, the carrier gas is selected from nitrogen, argon, or a mixture of nitrogen and argon; Optionally, the flow rate of the carrier gas is 100~200 sccm, preferably 130~170 sccm.
[0010] In an optional embodiment, the pressure in the plasma treatment chamber is 50~80 Pa, preferably 55~65 Pa.
[0011] In an optional implementation, the plasma treatment process has a power of 150~250W and a treatment time of 8~12min.
[0012] In an optional embodiment, the vapor deposition process uses tetraethyl orthosilicate as the silicon source, a deposition temperature of 350~450℃, a deposition pressure of 800~1200Pa, and a deposition time of 25~35min.
[0013] Secondly, the present invention provides a modified carbon fiber, which is prepared by any of the methods described in the foregoing embodiments.
[0014] Thirdly, the present invention provides a carbon fiber reinforced composite material, comprising a resin matrix and modified carbon fibers as described in the foregoing embodiments, which are compounded with the resin matrix. Optionally, the modified carbon fiber content in the carbon fiber reinforced composite is 55-65 vt%. Optionally, the resin matrix is epoxy resin, unsaturated polyester or bismaleimide resin, or a mixture of at least two of the aforementioned resins.
[0015] The present invention has the following beneficial effects: This invention provides a simple, highly controllable, and effective method for modifying the surface of carbon fibers. This method combines plasma pre-activation and chemical vapor deposition techniques to grow uniform nanoscale silica particles in situ on the carbon fiber surface, thereby synergistically improving its surface roughness and chemical activity, ultimately enhancing the interfacial properties of the carbon fiber composite material. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0017] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0018] Based on the current problem of unsatisfactory overall mechanical properties of carbon fiber composites, the inventors conducted the following research and considerations: If the gas phase oxidation method is used, oxygen-containing functional groups can be introduced by etching the fiber surface with air, ozone, etc. However, this method is violent, has a narrow process window, and is prone to over-etching, which can damage the strength of the fiber itself.
[0019] If liquid-phase oxidation is used, strong acids or strong oxidants such as nitric acid and hydrogen peroxide can be used to introduce active groups onto the surface of carbon fibers. However, this method has problems such as significant environmental pollution, complex processes, and difficulty in completely removing residual acid.
[0020] If a sizing method is used, a layer of polymer sizing agent is coated on the fiber surface, which can improve processing performance, but the improvement of interfacial chemical bonding is limited, and the sizing agent may have poor compatibility with certain resin matrices.
[0021] While nanoparticle modification methods, such as grafting carbon nanotubes or graphene, can effectively increase mechanical interlocking, they also present problems such as uneven nanoparticle dispersion, weak bonding with fibers, complex processes, and high costs.
[0022] Therefore, developing a process-controllable and efficient modification method that can effectively activate the surface chemical properties of carbon fibers, construct a stable microstructure, and cause minimal damage to the fiber matrix has significant industrial application value.
[0023] This invention provides a method for surface modification of carbon fibers, comprising: Carbon fibers are subjected to plasma treatment in a mixed atmosphere at a power of 50-500W (e.g., 50 W, 100 W, 200 W, 300 W, 400 W or 500 W) for 1-30 minutes (e.g., 1 minute, 5 minutes, 10 minutes, 20 minutes or 30 minutes) to obtain a pretreated product. The mixed atmosphere includes oxygen at a volume ratio of 1-18% (e.g., 1%, 5%, 8%, 10%, 15% or 18%). The pretreated sample was placed in a vapor deposition chamber, a silicon source was introduced, and nano-silica particles were deposited on the surface of the pretreated sample by vapor deposition. The deposition temperature was 200~600℃, the deposition pressure was 100~5000Pa, and the deposition time was 5~120min. After deposition, the carbon fibers were cooled to room temperature under an inert atmosphere to obtain surface-modified carbon fibers.
[0024] The surface modification method provided in this invention employs plasma treatment of carbon fibers, which ensures the introduction of a large number of active sites (such as carboxyl and hydroxyl groups) on the carbon fiber surface without excessive etching. This provides "anchor points" for the subsequent uniform and firm deposition of nano-SiO2. The introduction of nano-SiO2 significantly increases the surface roughness and specific surface area of the fiber, forming a multi-scale interface reinforcement structure. The active sites introduced by plasma treatment of carbon fibers can form strong chemical bonds with the resin matrix through chemical functional groups, and can also achieve physical bonding strengthening through the "pinning effect" and mechanical interlocking caused by nanoparticles. At the same time, plasma treatment of carbon fibers reduces the damage to the fiber body caused by high-current etching or strong acid.
[0025] Specifically, the preparation method is as follows: S1, Plasma Processing Carbon fibers are subjected to plasma treatment in a mixed atmosphere at a power of 50-500W for 1-30 minutes to obtain a pretreated product. The mixed atmosphere contains oxygen at a volume ratio of 1-18%.
[0026] In this step, without excessive etching of the carbon fiber, a large number of active sites (such as carboxyl groups and hydroxyl groups) are introduced on the surface of the carbon fiber through plasma, which provides "anchor points" for the uniform and firm deposition of nano-SiO2 in the future. At the same time, it can also form strong chemical bonds through chemical functional groups when the modified carbon fiber is combined with the resin.
[0027] This step uses plasma to treat carbon fibers. This method is gentle and significantly less intense than electrochemical oxidation or gas phase oxidation (where air, oxygen, or ozone directly etches the fiber). It will not cause excessive etching of the fiber, thus avoiding damage to the fiber's inherent strength. Compared to treating fibers with strong acids or alkalis, it will not pollute the environment or damage the fiber.
[0028] Optionally, the mixed atmosphere is a mixture of an active gas and an inert gas, wherein the active gas is at least one of air and oxygen; the volume ratio of the active gas to the inert gas is 1:5 to 20 (e.g., 1:5, 1:10, 1:15 or 1:20).
[0029] Optionally, the silicon source is selected from at least one of tetraethyl orthosilicate, silicon tetrachloride, and methyltriethoxysilane. To ensure better performance of the modified carbon fibers, tetraethyl orthosilicate is preferred as the silicon source.
[0030] Optionally, the silicon source is carried into the vapor deposition chamber by a carrier gas. Further, the silicon source is carried into the vapor deposition chamber by bubbling a carrier gas.
[0031] Optionally, the carrier gas is selected from nitrogen, argon, or a mixture of nitrogen and argon.
[0032] Optionally, the carrier gas flow rate is 100~200 sccm, preferably 130~170 sccm (e.g. 130 sccm, 150 sccm or 170 sccm).
[0033] Optionally, the plasma treatment chamber pressure is 50~80 Pa (e.g., 50 Pa, 60 Pa, 70 Pa or 80 Pa).
[0034] Preferably, to further ensure the introduction of more active sites onto the carbon fiber surface without causing excessive etching, the chamber pressure is 55~65Pa (e.g., 55Pa, 60Pa or 65Pa), the plasma treatment power is 150~250W (e.g., 150W, 200W or 250W), and the treatment time is 8~12min (e.g., 8min, 10min or 12min).
[0035] S2, vapor deposition The pretreated sample was placed in a vapor deposition chamber, and a silicon source was introduced. Nanoscale silica particles were deposited on the surface of the pretreated sample via vapor deposition. The deposition temperature was 200–600 °C (e.g., 200 °C, 300 °C, 400 °C, 500 °C, or 600 °C), the deposition pressure was 100–5000 Pa (e.g., 100 Pa, 500 Pa, 1000 Pa, 2000 Pa, 4000 Pa, or 5000 Pa), and the deposition time was 5–120 min (e.g., 5 min, 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, or 120 min). After deposition, the sample was cooled to room temperature under an inert atmosphere to obtain surface-modified carbon fibers. The obtained modified carbon fibers had a nanoscale silica particle size of 10–200 nm and an areal density of 10–200 particles / μm².
[0036] During vapor deposition, the silicon source decomposes into silica, which is deposited on the surface of carbon fibers after the introduction of active sites. The introduction of active sites on the carbon fiber surface provides "anchor points" for silica deposition, resulting in better bonding stability, density, and uniformity of the nano-silica.
[0037] Preferably, in order to ensure that the modified carbon fiber has better performance in all aspects, the silicon source in the vapor deposition process is preferably tetraethyl orthosilicate, the deposition temperature is 350~450℃ (e.g. 350℃, 400℃ or 450℃), the deposition pressure is 800~1200Pa (e.g. 800Pa, 1000Pa or 1200Pa), and the deposition time is 25~35min (e.g. 25min, 30min or 35min).
[0038] The modified carbon fiber provided in this embodiment of the invention is prepared using the method provided in this embodiment of the invention.
[0039] The carbon fiber reinforced composite material provided in this embodiment of the invention includes a resin matrix and modified carbon fibers compounded with the resin matrix.
[0040] The carbon fiber reinforced composite material provided by the present invention has high interlaminar shear strength because it includes the modified carbon fiber provided in the embodiments of the present invention.
[0041] Optionally, to improve the performance of the carbon fiber composite, the content of modified carbon fiber in the carbon fiber reinforced composite is 55-65 vt% (e.g., 55 vt%, 60 vt% or 65 vt%).
[0042] Optionally, the resin matrix is epoxy resin, unsaturated polyester or bismaleimide resin, or a mixture of at least two of the aforementioned resins.
[0043] Example 1 A bundle of T700 grade PAN-based carbon fiber was extracted with acetone using a Soxhlet extractor for 48 hours to remove the surface sizing agent, and then vacuum dried. It was placed in a parallel plate plasma reactor, and an argon-oxygen mixture (volume ratio 20:1) was introduced, maintaining the chamber pressure at 50 Pa. The radio frequency power supply was turned on, and the pretreated product was obtained after 1 minute of pretreatment at 50 W.
[0044] The pretreated sample was rapidly transferred to a tubular chemical vapor deposition furnace. Argon gas (flow rate 100 sccm) was used as the carrier gas, and tetraethyl orthosilicate (TEOS) vapor was bubbled into the reaction zone. The deposition temperature was set to 200°C, the system pressure to 100 Pa, and the deposition time to 5 min.
[0045] After deposition, the silicon source was turned off, and the fiber was naturally cooled to room temperature under a continuous argon flow. The modified carbon fiber A was then obtained. SEM characterization showed that SiO2 particles with a diameter of approximately 10–30 nm were uniformly attached to the fiber surface, with an areal density of approximately 15 particles / μm².
[0046] Example 2 The carbon fiber was cleaned in the same manner as in Example 1. The plasma pretreatment conditions were changed to: argon and air mixture (volume ratio 10:1), chamber pressure 80 Pa, processing power 500 W, and processing time 30 min.
[0047] In the deposition process, the silicon source was changed to silicon tetrachloride, and the carrier gas was nitrogen (flow rate 200 sccm). The deposition temperature was set to 600℃, the system pressure to 5000 Pa, and the deposition time to 120 min.
[0048] The modified carbon fiber B was obtained by cooling in the same manner as in Example 1. Characterization showed that the SiO2 particles grown on the fiber surface had a large particle size of approximately 150-200 nm and a high areal density of approximately 180 particles / μm².
[0049] Example 3 The carbon fiber was cleaned in the same manner as in Example 1. The plasma pretreatment conditions were: argon and oxygen mixture (volume ratio 10:1), chamber pressure 60 Pa, processing power 200 W, and processing time 10 min.
[0050] In the deposition process, the silicon source was TEOS, and the carrier gas was argon (flow rate 150 sccm). The deposition temperature was set at 400℃, the system pressure at 1000 Pa, and the deposition time at 30 min.
[0051] The modified carbon fiber C was obtained by cooling in the same manner as in Example 1. Characterization showed that the SiO2 particles on the fiber surface were uniformly distributed with a particle size of 50-80 nm and an areal density of approximately 80 particles / μm², exhibiting the best morphology.
[0052] Comparative Example 1 This comparative example is basically the same as Example 1, except that: Only the plasma treatment in Example 1 was performed, with the same parameters as in Example 1; no vapor deposition was performed, resulting in comparative carbon fiber D1.
[0053] Comparative Example 2 This comparative example is basically the same as Example 1, except that: Vapor deposition was performed without the plasma treatment described in Example 1, and the vapor deposition parameters were the same as in Example 1, resulting in comparative carbon fiber D2.
[0054] Comparative Example 3 This comparative example is basically the same as Example 1, except that: The plasma processing power was too high, at 600W, resulting in the comparison carbon fiber D3.
[0055] Comparative Example 4 This comparative example is basically the same as Example 1, except that: During plasma processing, the proportion of oxygen in the gas was too high, and the volume ratio of argon to oxygen was 4:1, resulting in the comparative carbon fiber D4.
[0056] Comparative Example 5 This comparative example is basically the same as Example 1, except that: During the vapor deposition process, the deposition temperature was 650℃, resulting in the comparative carbon fiber D5.
[0057] Comparative Example 6 This comparative example is basically the same as Example 1, except that: During the vapor deposition process, the deposition pressure was 5500 Pa, resulting in the comparative carbon fiber D6.
[0058] Comparative Example 7 This comparative example is basically the same as Example 1, except that: During the vapor deposition process, the deposition time was 150 min, and comparative carbon fiber D7 was obtained.
[0059] Comparative Example 8 The untreated raw fibers were compared with raw carbon fibers from the same batch that were only washed and dried with acetone as a control sample D8.
[0060] Experimental Example The modified carbon fibers obtained in the various embodiments and comparative examples were used to prepare carbon fiber / epoxy resin (EPON 828) unidirectional composite materials using the same process (pultrusion molding). The specific operation method and parameters of extrusion molding are referenced in GB / T27797.4.
[0061] A composite material with a fiber volume content of approximately 60% was obtained. Its interlaminar shear strength (ILSS) was tested according to ASTM D2344, and the results are shown in Table 1.
[0062] Table 1 Shear strength of composite materials made from various carbon fibers
[0063] As can be seen from the data in Table 1, the modified carbon fibers prepared in the embodiments of the present invention have significantly improved shear strength compared with the original fibers, especially in Example 3. The preparation parameters of Example 3 are the optimal parameters, achieving the best balance between chemical activity and physical roughness. The modified carbon fibers prepared in Example 3 have the highest shear strength when applied to the preparation of composite materials.
[0064] Comparing Comparative Example 1 with Example 1, Comparative Example 1 only underwent plasma treatment. Although its shear strength was improved due to enhanced surface activity compared to the original fiber, no nano-silica was deposited, and the degree of improvement was significantly worse than that of the various examples. Comparing Comparative Example 2 with Example 1, Comparative Example 2 only underwent silica deposition. Compared with the original fiber, due to its poor surface activity, less nano-silica was deposited, resulting in a very limited improvement in shear strength. Comparing Comparative Example 3 with Example 1, the power during plasma treatment in Comparative Example 3 was too high. Although the shear strength of Comparative Example 3 was improved compared to the original fiber, the degree of improvement was significantly worse than that of the other examples. This indicates that the power during plasma treatment should not be too high. Excessive power will cause damage to the fiber structure, thereby significantly reducing the interlaminar shear strength. Comparing Comparative Example 4 with Example 1, during the plasma treatment process of Comparative Example 4, the oxygen content in the atmosphere was too high, which led to an increase in the degree of fiber oxidation, damage to the surface structure, and the interlaminar shear strength was actually lower than that of the original fiber. Comparing Comparative Example 5 with Example 1, Comparative Example 5 had an excessively high vapor deposition temperature. Although it achieved an increase in shear strength compared to the original fiber, the degree of increase was significantly worse than that of the other examples. This indicates that the vapor deposition temperature should not be too high. Excessive temperature damages the surface structure of the carbon fiber, thereby reducing the interlaminar shear strength. Compared with Example 1, Comparative Example 6 had an excessively high vapor deposition pressure. Although the shear strength of Comparative Example 6 was improved compared with the original fiber, the degree of improvement was significantly worse than that of the other examples. This indicates that the vapor deposition pressure should not be too high. Excessive pressure causes the deposition of nano-silica on the surface of carbon fiber, resulting in a decrease in interfacial properties and a decrease in interlayer shear strength. Compared with Example 1, Comparative Example 7 had a longer vapor deposition time. Although the shear strength was improved compared with the original fiber, the excessive time resulted in the deposition of too much nano-silica, which in turn reduced the shear strength.
[0065] In summary, the carbon fiber surface modification method provided in this invention has the following characteristics: 1. The synergistic effect of plasma pre-activation and chemical vapor deposition (CVD) technology: Plasma pretreatment introduces a large number of active sites (such as carboxyl and hydroxyl groups) on the fiber surface without excessive etching, providing "anchor points" for the subsequent uniform and firm deposition of nano-SiO2. The introduction of nano-SiO2 significantly increases the surface roughness and specific surface area of the fiber, forming a multi-scale interface reinforcement structure.
[0066] 2. The interface bonding mode between carbon fiber and resin is optimized. The modified carbon fiber surface can form strong chemical bonds with the resin matrix through chemical functional groups, and can also achieve physical bonding enhancement through the "pinning effect" and mechanical interlocking caused by nanoparticles.
[0067] 3. Controllable process with minimal damage: Plasma is used, avoiding damage to the fiber matrix caused by high temperatures or strong acids. Vapor deposition parameters can be precisely controlled, thereby controlling the size, density, and morphology of nanoparticles and enabling designable interface properties.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for surface modification of carbon fiber, characterized in that, include: Carbon fibers are subjected to plasma treatment in a mixed atmosphere at a power of 50-500W for 1-30 minutes to obtain a pretreated product. The mixed atmosphere includes oxygen at a volume ratio of 1-18%. The pretreated sample was placed in a vapor deposition chamber, a silicon source was introduced, and nano-silica particles were deposited on the surface of the pretreated sample by vapor deposition. The deposition temperature was 200~600℃, the deposition pressure was 100~5000 Pa, and the deposition time was 5~120 min. After deposition, the carbon fibers were cooled to room temperature under an inert atmosphere to obtain surface-modified carbon fibers.
2. The surface modification method according to claim 1, characterized in that, The mixed atmosphere is a mixture of an active gas and an inert gas, wherein the active gas is at least one of air and oxygen; The volume ratio of the active gas to the inert gas is 1:5~20.
3. The surface modification method according to claim 1, characterized in that, The silicon source is selected from at least one of tetraethyl orthosilicate, silicon tetrachloride, and methyltriethoxysilane.
4. The surface modification method according to claim 1, characterized in that, The silicon source is carried into the vapor deposition chamber by a carrier gas; Optionally, the silicon source is carried into the vapor deposition chamber by a carrier gas bubble.
5. The surface modification method according to claim 4, characterized in that, The carrier gas is selected from nitrogen, argon, or a mixture of nitrogen and argon; Optionally, the flow rate of the carrier gas is 100~200 sccm, preferably 130~170 sccm.
6. The surface modification method according to claim 1, characterized in that, The pressure in the plasma treatment chamber is 50~80 Pa, preferably 55~65 Pa.
7. The surface modification method according to claim 1, characterized in that, The plasma treatment process has a power of 150~250W and a treatment time of 8~12min.
8. The surface modification method according to claim 1, characterized in that, In the vapor deposition process, the silicon source is at least one of tetraethyl orthosilicate, silicon tetrachloride, and methyltriethoxysilane; the deposition temperature is 350~450℃; the deposition pressure is 800~1200Pa; and the deposition time is 25~35min.
9. A modified carbon fiber, characterized in that, It is prepared by the method described in any one of claims 1 to 8.
10. A carbon fiber reinforced composite material, characterized in that, It includes a resin matrix and the modified carbon fiber as described in claim 9, which is compounded with the resin matrix; Optionally, the modified carbon fiber content in the carbon fiber reinforced composite material is 55-65 vt%. Optionally, the resin matrix is epoxy resin, unsaturated polyester or bismaleimide resin, or a mixture of at least two of the aforementioned resins.